1987
DOI: 10.1017/s0003356100018535
|View full text |Cite
|
Sign up to set email alerts
|

Effects of offering silage overnight in the early grazing season to autumn-calved cows

Abstract: Three experiments were conducted in the early grazing seasons of 1982–84 inclusive. Autumn-calved lactating British Friesian cows grazed a perennial ryegrass pasture either by strip grazing to leave 80 mm residual herbage (SG) or by rotationally grazing six paddocks on a fixed pre-determined cycle (PG). They were offered grazing only or grazing and average quality grass silage (S) or a 1: 1 mix of silage and ensiled brewers' grains (SB) given individually overnight in a cubicle house.In experiment 1, cows rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
2

Year Published

1990
1990
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 8 publications
2
8
2
Order By: Relevance
“…Intakes of silage during the period of housing at night (6·6 and 5·6 kg DM per cow per day in Experiments 1 and 2 respectively) were similar to those recorded in previous studies (Aston et al. , 1987; Roberts and Kelly, 1990).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Intakes of silage during the period of housing at night (6·6 and 5·6 kg DM per cow per day in Experiments 1 and 2 respectively) were similar to those recorded in previous studies (Aston et al. , 1987; Roberts and Kelly, 1990).…”
Section: Discussionsupporting
confidence: 87%
“…The data on sward heights confirm that the proportional reduction in paddock size of 0·38 on treatment PG, compared to treatment CG, allowed similar grazing intensities to be achieved on both treatments. Nevertheless, in both experiments stocking rates at pasture on treatment PG were considerably lower than those recorded by Aston et al. (1987) for cows offered silage at night, namely 11·0–11·6 cows ha −1 .…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…(1989) report that each kilogram of added silage DM decreases HDMI by 0.63 kg in steers. Additionally, Aston et al . (1987) suggested that offering silage raises the concentration of fat in the milk and depresses the yields of milk and protein in grazing cows.…”
Section: Discussionmentioning
confidence: 99%